Validation of the INCREMENT‐SOT‐CPE score in a large cohort of liver transplant recipients with carbapenem‐resistant Enterobacterales infection. Issue 2 (7th March 2023) - Rinaldi, Matteo; Bonazzetti, Cecilia; Gallo, Mena; Ferraro, Giuseppe; Freire, Maristela; Terrabuio, Débora Raquel Benedita; Tandoi, Francesco; Romagnoli, Renato; De Rosa, Francesco Giuseppe; Mularoni, Alessandra; Ferrarese, Alberto; Burra, Patrizia; et al.
Abstract: Background: Management of infections due to carbapenemase‐resistant Enterobacterales (CRE) in solid organ transplant (SOT) recipients remains a difficult challenge. The INCREMENT‐SOT‐CPE score has been specifically developed from SOT recipients to stratify mortality risk, but an external validation is lacking. Methods: Multicenter retrospective cohort study of liver transplant (LT) recipients colonized with CRE infection who developed infection after transplant over 7‐year period. Primary endpoint was all‐cause 30‐day mortality from infection onset. A comparison between INCREMENT‐SOT‐CPE and other selected scores was performed. A two‐level mixed effects logistic regression model with random effects for the center was fitted. Performance characteristics at optimal cut‐point were calculated. Multivariable Cox regression analysis of risk factors for all‐cause 30‐day mortality was carried out. Results: Overall, 250 CRE carriers developed infection after LT and were analyzed. The median age was 55 years (interquartile range [IQR]: 46–62) and 157 were males (62.8%). All‐cause 30‐day mortality was 35.6%. A sequential organ failure assessment (SOFA) score ≥ 11 showed a sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy of 69.7%, 76.4%, 62.0%, 82.0%, and 74.0%, respectively. An INCREMENT‐SOT‐CPE ≥ 11 reported a sensitivity, specificity, PPV, NPV, and accuracy of 73.0%, 62.1%, 51.6%, 80.6% and 66.0%, respectively. At multivariable analysis acute renal failure, prolonged mechanical ventilation, INCREMENT‐SOT‐CPE score ≥ 11 and SOFA score ≥ 11 were independently associated with all‐cause 30‐day mortality, while a tigecycline‐based targeted regimen was found to be protective. Conclusions: Both INCREMENT‐SOT‐CPE ≥ 11 and SOFA ≥ 11 were identified as strong predictors of all‐cause 30‐day mortality in a large cohort of CRE carriers developing infection after LT. Abstract : We evaluated the prognostic role of the INCREMENT‐SOT‐CPE score, specifically developed from SOT recipients, and other main scores to stratify mortality risk. Our results suggest that both INCREMENT‐SOT‐CPE ≥ 11 and SOFA ≥ 11 are strong predictors of all‐cause 30‐day mortality in a cohort of CRE carriers developing infection after liver transplant.